Effect of dietary protein on post‐prandial glucose in patients with type 1 diabetes. Issue 6 (22nd March 2013) - Borie‐Swinburne, C.; Sola‐Gazagnes, A.; Gonfroy‐Leymarie, C.; Boillot, J.; Boitard, C.; Larger, E.
Abstract Background In flexible insulin therapy, determination of the prandial insulin dose only takes into account the carbohydrate content of the evening meal, and not the protein content. Protein can, however, contribute to gluconeogenesis. We compared the glycaemic effect of a standard evening meal with that of a test evening meal enriched in protein. Methods The present study was conducted in 28 C‐peptide negative patients with type 1 diabetes. Two evening meals that were similar in content, except that one was enriched by the addition of 300 g of 0%‐fat fromage frais, were taken on two consecutive days. Insulin doses were maintained exactly the same before both evening meals. Patients were monitored with a continuous glucose‐monitoring device. Results Patients ate similar quantities at both evening meals, except for protein (21.5 g more at the test evening meal). The preprandial insulin dose was 0.96 (0.4) U per 10 g carbohydrates. After correction for differences of interstitial glucose at the start of the evening meals, both interstitial and capillary glucose levels were similar after both evening meals, except for the late‐post‐prandial interstitial glucose level. Conclusions We found no effect of dietary protein on post‐prandial‐, overnight‐ or late‐night glucose levels in patients with type 1 diabetes. This confirms that dietary proteins need not be included in the calculation of prandial insulin dose.